A DEFINIÇÃO DE UMA ONTOLOGIA PARA INTEGRAR DADOS DE INTERATOMA E TRANSCRIPTOMA DE CÂNCER - Cabral, Heleno Carmo Borges (2010)
Ontocancro is an ontology stored in a knowledge database designed to be a source of information to integrate transcriptomics and interatomics data involved in gene pathways of genome maintenance/stability mechanisms (GMM). Genome maintenance mechanisms are shown to be critical for cell homeostasis since their malfunctioning can predispose to cancer. Repair, apoptosis and chromosome stability pathways comprise the cornerstone of GMM. The information about these pathways are disseminated in various databases as NCI-Nature, BioCarta, KEGG, Reactome, Prosite, GO and others. Ontocancro was created with the intention of integratin the information of genes involved in GMM from several curated databases. This data integration is difficult for biological data lack a unified vocabulary and need constant update what is provided by Ontocancro. Additionally, it allows the integration of transcriptome data provided by some Affymetrix microarrays platforms with interactome data from the STRING database, which has information about protein interactions. So, this work shows the integration of data from biological information systems using the ontology paradigm, in order to integrate transcriptomics and interatomics data involved in gene pathways of genome stability.